Twenty-five Years of the Journal of Global Information Technology Management: A Bibliometric Analysis - Biswas, Baidyanath (My University, 2023)
The Journal of Global Information Technology Management (JGITM) is an established and globally reputed journal in the Information Technology area, focusing on publishing international IS research. It is international in all respects: content, authors’ origin, readers’ origin, and the editorial board. The journal was established in January 1998 and completed 25 years of publication in 2022. In celebration, this study presents a comprehensive and historical overview of the leading trends of the journal since its inception. The bibliographic data was retrieved from the Scopus database and analysed with the help of the R software. This analysis considers indicators such as the most cited articles, productive authors, influential authors, leading institutes, top countries publishing in JGITM, co-citation networks, and keyword analysis. The study also develops a graphical visualisation of the networks of bibliographic data. This graphical visual helps to analyse co-citation and bibliographic coupling among the published research studies. Our results indicate a continuous and substantial increase in the quality of publications, impact factor, and a growing interest in publishing articles in the journal by a broader community of academicians and scholars. We hope this information will be of significant value to JGITM’s audience: the readers and past and future authors.
Keywords: Publication trends; Bibliometric analysis; Scientometric analysis; Network analysis; Co-citation networks; Digital Engagement; Digital Humanities; Developing Countries; Social media and social networking